The Concept of Construction of Hybrid Constructed Wetland for Wastewater Treatment in Roztocze National Park - Krzysztof Jóźwiakowski; Michał Marzec; Magdalena Gizińska-Górna; Aneta Pytka; Anna Skwarzyńska; Tomasz Słowik; Alina Kowalczyk-Juśko; Magdalena Gajewska; Aleksandra Steszuk; Tadeusz Grabowski; Zbigniew Szawara (Barometr Regionalny)
Roztocze National Park (RNP) is one of 23 national parks in Poland. It was created in 1974 both to protect the natural and cultural heritage as well as to share the park area for science, education and tourism. In caring for the environment, the park removed asbestos coverage, performs thermo-modernization using renewable energy sources by the installation of solar panels and photovoltaic cells on the roofs of buildings, and pellet stoves are installed in boiler rooms. Part of these actions includes the application of innovative technologies for water and wastewater, related to e.g. recovery of rainwater for washing cars and the construction of wastewater treatment wetlands. RNP has been spreading for many years the knowledge about the methods used to most effectively care for the natural environment. Constructed wetland (CW) technology could be one of such methods. The current research shows that facilities working in CW technology provide high pollutant removal and full guarantee of high ecological impact with low operating cost, so they can be used to protect the aquatic environment in protected areas and valuable landscapes. The paper presents a concept of solving the problems of wastewater treatment by means of using hybrid constructed wetland in three villages in the forest of Roztocze National Park. The advantages of the proposed technology are easy and simple operation, high resistance to irregular supply of water treatment and very low operating costs compared to conventional solutions. The natural look of CWs allows easy incorporation into the existing landscape.